Development on Evaluation Criteria of Environmental Health Management: A Case Study of Community-Based Whitewater Rafting Tourism Sites in Trang Province - Ruangdej Chaosuansreecharoen, Kannika; Pongkaset, Anchalee; Loakaewnoo, Treechart; Akharawirawat, Thanapanan; Hlupo, Wittaya; Kongsanit, Saowalak; Chaosuansreecharoen, Paiboon; Srilaong, Adisak (Health Science Journal of Thailand, 2025)
This study aimed to develop an environmental health management assessment criterion specifically for community-based whitewater rafting tourism sites in Trang Province, as no such specific criteria currently exist. A mixed-methods research design was employed, incorporating qualitative data collected from 22 environmental health experts using a two-round Delphi technique, and quantitative data collected from 400 tourists for first-order confirmatory factor analysis (CFA). Data collection was conducted using questionnaires. The data were analyzed through content analysis, median, interquartile range, and first-order CFA. The findings revealed that the developed assessment criteria comprised 12 categories with a total of 131 sub-indicators. The factor loadings of the indicators within each category ranged from 0.44 to 0.99, indicating appropriate clustering of the indicators and structural validity of the assessment tool. The developed criteria can serve as a self-assessment tool for community-based tourism sites to enhance environmental health quality, and can also be used as a foundation for certification by relevant authorities in an efficient manner.